Mapeamento do Eucalipto no Estado de Minas Gerais Utilizando o Sensor Modis / Using Modis Sensoring to Map Eucalyptus Production in the State of Minas Gerais - Borges, Mariley Gonçalves (2018)
MODIS remote sensing permits mapping Vegetation Index Normalized Difference -- NDVI and Vegetation Index Revamped -- EVI that monitor vegetated and non-vegetated areas. The objective of this study is to map the expansion of eucalyptus planting in Minas Gerais State using vegetation indices provided by MODIS remote sensing. Expansion of area in eucalyptus is monitored, a database update obtained and checked for quality using low spatial resolution sensing which produces vegetation indices. Although NDVI and EVI presented limitations for classifying kinds of eucalyptus present, EVI presented satisfactory results in mapping eucalyptus area for 2007 and 2015.